“Picking the right person … can make or break the whole deal”: Development of a layperson injector selection tool for administration of home-based long-acting injectable antiretroviral therapies - Beth Bourdeau; Alicia T. Bolton; Michelle Palomares; Jonathan Van Nuys; Erin Moore; Gregory M. Rebchook; Mallory O. Johnson; Starley B. Shade; Jesse O’Shea; Kate Buchacz; Kashif Iqbal; Parya Saberi (PLoS ONE, 2026)
Background Clinic-based administration of long-acting injectable antiretroviral therapy (LAI-ART) is resource-intensive and may exacerbate disparities in access to care. Home-based administration by trained layperson injectors, or treatment buddies (TBYs), could expand access to LAI-ART; however, maintaining high-quality clinical care requires selecting suitable TBYs for its implementation. This paper describes the development of the TBY Selection Tool to support people with HIV (PWH) in identifying appropriate TBYs. Methods The tool development process consisted of 5 phases. In Phase 1, semi-structured interviews were conducted with 19 clinicians, 16 PWH, and 15 candidate TBYs. Transcripts were thematically coded to identify domains influencing TBY suitability. In Phase 2, draft items were developed and refined into a structured survey. In Phase 3, 7 PWH completed the tool during a 2-month pilot. In Phase 4, a Community Advisory Panel (CAP) (n = 10) reviewed items for clarity, relevance, and comprehensiveness. In Phase 5, feedback was incorporated to finalize the tool. Results Clinicians emphasized the reliability of TBYs, the confidentiality of home-based injections, and the importance of adhering to injection schedules. PWH prioritized trust in the TBYs, TBY availability, and comfort with bodily intimacy. TBYs highlighted emotional steadiness, willingness to learn, and responsibility for continuity of care. These domains were operationalized into a survey assessing relationship history, reliability, confidentiality, availability, proximity, and comfort with injections. Pilot testing showed 100% completion without difficulties. CAP feedback led to refined wording, expanded response options, and clearer phrasing, which were used to finalize a 12-item survey. Conclusions The TBY Selection Tool provides a structured framework to support PWH in identifying appropriate TBYs for home-based LAI-ART. By integrating clinical, individual, and community perspectives, the tool addresses factors important for the safe, acceptable, and feasible implementation of home-based LAI-ART. Psychometric assessment, scoring, and further validation in larger, more diverse populations is needed.